Exercise for People with Acquired Brain Injury: An ICF Perspective - Marta Pérez-Rodríguez; Juan José García-Hernández; Saleky García-Gómez; Javier Pérez-Tejero (Applied Sciences, 2022)
Exercise is an important element in the process of recovery from an acquired brain injury (ABI). However, specific guidance for exercise prescription and interventions in this population are missed. The aim of this study was to establish the key parameters to design and implement exercise programs based on the International Classification of Functioning, Disability, and Health (ICF) domains. A panel of experts that consisted of 13 professionals from neuro-rehabilitation centers evaluated the key parameters of this original proposal. The Heinemann methodology was used for all qualitative analyses. Additionally, Cronbach’s alpha was applied to the statistical analyses. According to the results, Cronbach’s alpha (0.97) indicated excellent internal consistency, and the experts perceptions ratified the proposed criteria to develop exercise programs for people with ABI. The proposed key parameters for the development of exercise programs for people with ABI based in ICF domains (body functions, activity—participation and environmental factors) bring a new, solid, and innovative tool for methodological design of these programs in sub-acute and chronic rehabilitation settings.